2012
DOI: 10.5114/ninp.2012.27180
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of Trichosporon brain abscess, successfully treated with surgical excision and antifungal agents

Abstract: Trichosporonosis is an acute, sometimes fatal infection with the potential capability of disseminating to multiple deep organs. More than 100 cases of trichosporonosis have been described, particularly in patients with neutropenia or haematological malignancies. In 1970, Watson et al. described the first case of brain trichosporonosis; the patient died 4 weeks after admission. Herein, we describe a 34-year-old man with a history of autoimmune hepatitis, hypothyroidism, and alopecia totalis, treated with cortic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…In the current study, the most prevalent species isolated from clinical samples was C. albicans, followed by C. parapsilosis, C. tropicalis, and C. guilliermondii. Moreover, some uncommon yeasts including C. africana, T. asahii, and C. jirovecii isolated in the current study that were less reported from Iran so far (24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 56%
“…In the current study, the most prevalent species isolated from clinical samples was C. albicans, followed by C. parapsilosis, C. tropicalis, and C. guilliermondii. Moreover, some uncommon yeasts including C. africana, T. asahii, and C. jirovecii isolated in the current study that were less reported from Iran so far (24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 56%
“…CNS trichosporonosis is uncommon in both the immunocompromised and the immunocompetent host. Reports of this condition in the literature are limited to case reports (5,(7)(8)(9). CNS trichosporonosis is usually fatal.…”
Section: Discussionmentioning
confidence: 99%
“…Central nervous system (CNS) trichosporonosis is a rare clinical manifestation associated with immunocompromised patients [ 18 ]. In fact, only a few clinical cases of this medical condition have been reported in the literature [ 2 , 4 , 18 25 ] and none of them was due to T. inkin .…”
Section: Introductionmentioning
confidence: 99%
“…Despite some controversies, triazoles appear to be the best first line antifungal therapy for invasive trichosporonosis, especially when T. asahii is involved [ 1 , 10 , 18 , 19 , 27 ]. In vitro studies suggest that voriconazole exhibits the best antifungal activity against different Trichosporon species, when compared to amphotericin B and fluconazole [ 10 ].…”
Section: Introductionmentioning
confidence: 99%